PENGARUH TERAPI PSIKOEDUKASI TERHADAP BEBAN DAN KEMAMPUAN KELUARGA DALAM MERAWAT ANAK AUTIS DI KOTA SOLOK TAHUN 2017. - Damaiyanti, Siska (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
Autism is a disorder that occurs in children who are marked by developmental delays in cognitivefields, communication, interest in social interaction, and behavior and children are only interestedin their own mental activities. West Sumatra to date has not had official data about autisticpatients, due to the presence of autistic children do not stay each semester. Autism search results in2015 as many as 301 children with autism in all SLB Padang city (West Sumatra Education &Culture, 2015). The population in this study is the family caring for autistic children in Solok city,amounting to 106 people. With a sample size of 42 for control and 42 for the intervention groupThe sampling technique in the study was proportional random sampling. Sampling is done inproportion by taking the subject. The result of family characteristic analysis in the interventiongroup from 42 respondents, middle age category was 20 people (23,8%), female 38 people(45,2%), average of middle and junior high education respondents was 31 people (36.9%),respondents who work 27 people (32.1%), as many as 37 people (44.0%) are direct parents whocare for the autistic child itself. In the control group of 42 respondents, the middle age categorywas 20 people (23.8%), female (36.8%), the average of middle and junior high school educationwas 37 people (44 , 0%), respondents who work 31 people (36.9%), as many as 34 people (40.4%)are direct parents who care for autistic children themselves.Keywords: Eutism, psicoeduction, familyReference: 92 (2000-2016)